STRATEGI PENINGKATAN KUALITAS PELAYANAN PDAM KABUPATEN GRESIK - Dwi Wahyu Prasetyono; Armina Diana (FISIP UWP, 2022)
The purpose of this study was to determine the strategy for improving the service quality of PDAM Kab. Gresik and to find out strategic recommendations to improve the service quality of PDAM Kab. Gresik. The background of this research is the number of complaints from customers to PDAM Kab. Gresik as these complaints have the same point but have not been resolved optimally. This study uses a qualitative research method with a descriptive approach. The research location is at the Head Office of the Giri Tirta Regional Drinking Water Company, Gresik Regency. Data collection techniques through interviews, documentation, and observation. The focus of the research is the service quality strategy, while the research dimension used is the quality of service by parasuraman with 5 dimensions, namely Direct Evidence, Reliability, Responsiveness, Assurance, and using SWOT Analysis. Testing the 5 dimensions of Empathy which has a weak point from the dimensions of reliability, responsiveness, and empathy that many customers complain about and the results of the SWOT analysis, namely Strength includes the availability of online services so that you don't have to come to the office. The weakness is that the complaint service information system has not functioned optimally. The opportunity is not having the competitiveness of any party, whether private or government. The threat is that there is a slow response given by the complaint service officer so that the level of complaints is getting higher. The conclusion of this study is that the service quality of PDAM Giri Tirta is still not good when viewed from the strengths, weaknesses, opportunities and threats so that the researchers recommend strategies, namely creating automating quality, developing / upgrading service information systems, educating consumers about complaint services, developing a quality culture, adding qualified technical personnel (HR).